Pengembangan LKPD Interaktif Berbasis STEAM pada Kompetensi Pengetahuan IPS Siswa Kelas V di SD No. 3 Sibanggede - Ni Luh Venny Eka Riyani; I Gusti Agung Ayu Wulandari (Universitas Batanghari Jambi, 2022)
The problem that occurs is the use of LKPD that has not been maximized in the learning process. LKPD used in the learning process only comes from.The student worksheets are not interactive, so that it has an impact on the low learning outcomes for the social studies content of the fifth grade students at SD No. 3 Sibanggede. In this study, data collection was carried out using test methods in the form of objective tests and non-test methods in the form of unstructured interviews, observations and questionnaires. The techniques of qualitative descriptive analysis, quantitative descriptive analysis and inferential statistical analysis (t-test sample dependent) were used to analyze the data obtained. This study uses the ADDIE model. The results of the research obtained are the development of STEAM-based interactive student worksheet using the ADDIE model, the results of the interactive student worksheet feasibility test based on the results reviews are of subject content expert 93.75% with very good qualifications, the results review are of the learning design expert 87.50% with good qualifications, the results of the review expertof learning media are 90.00% with very good qualifications, the results of individual trials are 90.00% with very good qualifications, the results of small group trials are 91.66% with very good qualifications and the results of field trials are 88, 40% with good qualifications. Based on the results of the t- test, it is obtained that with db = n 1 = 25− 1 = 24, ttablet of significance 5% = 1,711, it can be seen that tcount > ttable. So that rejected accepted. This means that interactive student worksheets are effective in improving Social Studies learning outcomes for fifth grade elementary school.